The Reproduction and Circulation of Knowledge in Islamic Civilization: An Example from Fifteenth-Century Samarqand - Mehmet Arıkan (Nazariyat: Journal for the History of Islamic Philosophy and Sciences, 2017)
“History begins with writing,” because writing is the most important and reliable tool for transmitting knowledge to future generations. It has made use of various materials for this very purpose for centuries and one of these materials is paper. The transmission of paper to the Islamic world and its subsequent vast production allowed books to become widespread and made paper the most important medium for written transmissions. We do not have a great deal of first-hand information on how books were prepared other than the compilation process which we know due to the presence of some compilers’ anecdotes regarding the characteristics of the compilation which is an aspect of its meaning. However, producing a book as a commodity is just as important as compilation in the sense of reproduction and circulation of knowledge. This article introduces the accounts of ʿAbd al-Razzāq al-Tirmidhī, a copyist who was fully engaged in the copying stage of book production. The intellectual and scientific life of the period will be discussed based on his list, which was recorded on the last page of a copy of the Mathnawī written in Samarqand in 1417. Several questions will also be raised for future studies.